Women's political participation in Sarawak : methodology,fieldwork and findings / Nadrawina Haji Isnin - Haji Isnin, Nadrawina (Universiti Teknologi MARA, Shah Alam, 2012)
This article critically evaluates an agenda for political participation research aimed at providing empirical answers to questions derived from the women in Sarawak. Among other issues, this paper explores the gender constructs that impede women's access to the higher political sphere. Indeed, such socially constructed realities often diminish the possibility for women involvement in the process of decision making. Of particular emphasis on this paper, is the facilitating factor that propels women's entry into political parties. Some of these issues are compromised or became obstacles in women's opportunity in political life. The empirical questions are drawn together into an integrated agenda for future studies in gender and political participation in Sarawak.